Postgraduate Dissertation Assessment: Exploring Extant Use and Potential Efficacy of Visualisations - Van Biljon, Judy; Renaud, Karen (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2015)
In the context of assessment, two specific challenges face South African academics. The first is that their universities have experienced an unprecedented increase in postgraduate students without a concomitant increase in supervision capacity. The second challenge is that many South African students are studying in a second or third language and struggle to express themselves in English. It is notoriously difficult to write text that is easy to read. Examiners are thus finding it challenging to maintain their own existing high standards of consistency, accuracy and fairness. This paper focuses on identifying a way of making the assessment of dissertations more efficient, while retaining rigour and fairness. In so doing, we want to provide students with a tool that will help them to communicate their research more effectively. In seeking an intervention, we noted the emerging use of visualisation as a communication facilitator in other areas of academia. Given the innate human ability to understand and remember visual representations, and the deep level of cognitive processing required to produce such visualisations, the considered inclusion of visualisations could be the means we are seeking. In this paper we report on an investigation into the extant use and potential usefulness of visualisation in a number of dissertations. We also explore supervisor expectations with respect to the use of visualisation in research reporting. Based on our findings, we propose that a discourse be opened into the deliberate use of visualisation in postgraduate research reporting.
Keywords: visualisation, assessment, postgraduate, dissertation